ELEMENTS OF ORGANISATIONAL CULTURE AS DETERMINING FACTORS IN THE SHAPING OF MODERN HIGHER EDUCATION INSTITUTIONS - Ziemkiewicz-Gawlik, Ilona; Miętkiewicz, Monika; Brzychcy, Katarzyna; Jaroszewski, Karol (Management and Administration Journal, 2024)
In modern society, educators who hold specific positions are expected to display practical knowledge as well as a theoretical basis, which students acquire in the process of education. Higher education institutions in Poland offer a wide range of programmes. People who want to receive an education can choose between public and non-public higher education institutions which offer full-time, extramural, part-time as well as hybrid (a combination of traditional and distance learning) and online programmes (distance learning). It needs to be highlighted that education quality at higher education institutions depends primarily on qualified and engaged staff. Regardless of the choice they make, young people who graduate from secondary school either go to work or continue their education. This area provides the basic cognitive processes described by the authors, i.e. education, improvement and (further) training. The aim of the article is to identify the external factors determining the shaping of organisational culture at the university in the opinion of students, as well as to present recommended changes in this area. The authors focus on internal factors which shape the organisational culture of higher education institutions, and which determine education quality as well as the entire relevant system. The conducted studies refer to selected internal factors which shape the organisational culture of public and non-public higher education institutions which offer practical programmes. Recommendations for changes in the studied areas are subsequently presented.